2009
DOI: 10.1177/1352458508101937
|View full text |Cite
|
Sign up to set email alerts
|

Does multiple sclerosis increase risk of adverse pregnancy outcomes? A population-based study

Abstract: Our study documents increased the risk of adverse pregnancy outcomes for mothers with MS, highlighting a need for more intensive monitoring and obstetric care during pregnancy. Future studies should explore the distinct manifestations and mechanisms of MS in diverse ethnic groups, so more complete information can be provided to affected women concerning pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
66
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 21 publications
10
66
1
Order By: Relevance
“…In contrast, in population-based studies from Norway, women with MS were at increased risk of cesarean delivery (though planned and not due to emergencies) and giving birth to SGA babies or with lower mean birth weight [74]. An increased risk of SGA babies and cesarean delivery was also detected in a population-based study from Taiwan [75]. In addition, Taiwanese MS patients were more likely to have preterm delivery.…”
Section: Prevalence Isotype Distribution and Clinical Associations mentioning
confidence: 73%
“…In contrast, in population-based studies from Norway, women with MS were at increased risk of cesarean delivery (though planned and not due to emergencies) and giving birth to SGA babies or with lower mean birth weight [74]. An increased risk of SGA babies and cesarean delivery was also detected in a population-based study from Taiwan [75]. In addition, Taiwanese MS patients were more likely to have preterm delivery.…”
Section: Prevalence Isotype Distribution and Clinical Associations mentioning
confidence: 73%
“…34 The effect of MS on pregnancy outcome includes increased risk of fetal growth restriction (odds ratio 35 These findings were confirmed in a smaller Taiwanese study (nϭ174), which, unlike the U.S. study, also found an increase in preterm birth (OR 2.25, 95% CI 1.37-3.70). 36 The mechanisms for increased rates of adverse pregnancy outcomes in women with MS are not clear.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…These factors included the characteristics of the mother: age (Cleary-Goldman et al, 2005), highest educational level (Chen et al, 2009), marital status (Kirchengast et al, 2007), year of delivery), infant gender (Ingemarsson, 2003;Di Renzo et al, 2007), parity and monthly family income . Maternal age was grouped into the following : ,20, 20 -24, 25 -29, 30 -34, 35-39 and 40.…”
Section: Variables Of Interestmentioning
confidence: 99%